Inventory of Weed Types on Clove Plants (Syzygium aromaticum L.) with Different Altitudes in Waai Village, Salahutu District, Central Maluku. - Elia L. Madubun; Abdul Karim Kilkoda; Imelda Grace Walasary (Faculty of Agriculture, Pattimura University, 2023)
This study aims to determine the dominant type of weed in the clove plantation area at an altitude of 63 m above sea level and 120 meters above sea level. This study uses a purposive sampling method of vegetation analysis with a sample plot of 1m´1m. The results showed that at an altitude of 63 m dpl found 23 types of weeds from 16 families consisting of 12 types of broad leaf weeds (broad leaf) from 11 families, 5 types of grass weeds (grass) from 3 families, 2 types of tekian weeds (cyperaceae). from 1 tribe, 2 types of ornamental plants from 2 tribes and 2 types of fern weeds from 2 tribes. Meanwhile, at an altitude of 120 m above sea level, 26 types of weeds were found from 22 tribes consisting of 13 types of broad leaf weeds from 12 families, 4 types of grass weeds (grasses) from 4 families, 5 species of fern weeds (fern) from 4 tribes. , 1 type of fern weed from 1 tribe and 3 types of tekian weed from 1 tribe.